The rage in Singapore schools : bullying. - Lee, Michelle Xiang Hui. (2008)
Includes Appendices: 1 feature writing. In the course of this project, we often found ourselves having to explain our choice of school bullying as the topic of our feature article. Fellow students and family alike commented that bullying is “a perennial problem” and “something everyone grows out of”, and thus reasoned that it was not a significant issue to pursue.